2015
DOI: 10.1038/bjc.2015.345
|View full text |Cite
|
Sign up to set email alerts
|

Targeted NF1 cancer therapeutics with multiple modes of action: small molecule hormone-like agents resembling the natural anticancer metabolite, 2-methoxyoestradiol

Abstract: Background:Both the number and size of tumours in NF1 patients increase in response to the rise in steroid hormones seen at puberty and during pregnancy. The size of tumours decreases after delivery, suggesting that hormone-targeting therapy might provide a viable new NF1 treatment approach. Our earlier studies demonstrated that human NF1 tumour cell lines either went through apoptosis or ceased growth in the presence of 2-methoxyoestradiol (2ME2), a naturally occurring anticancer metabolite of 17-β estradiol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Derivatives of 2-ME such as STX 3451 and STX 2895 are nonsteroidal chimeric microtubule disruptors which bind to the colchicine binding site leading to microtubule disruption by inhibiting tubulin assembly, which contributes to the compounds’ anti-proliferative effects. 21 , 24 Shen et al 21 demonstrated that both STX 3451 and STX 2895 reduced cell viability in ST88 human malignant peripheral nerve sheath tumor cells (MPNST) and induced cell death at a 10-fold lower concentration than 2-ME. Furthermore, STX 3451 treatment not only caused microtubule disruption but also affected the actin-based cytoskeleton through disruption of the long microfilaments and reorganization of actin molecules through depolymerization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Derivatives of 2-ME such as STX 3451 and STX 2895 are nonsteroidal chimeric microtubule disruptors which bind to the colchicine binding site leading to microtubule disruption by inhibiting tubulin assembly, which contributes to the compounds’ anti-proliferative effects. 21 , 24 Shen et al 21 demonstrated that both STX 3451 and STX 2895 reduced cell viability in ST88 human malignant peripheral nerve sheath tumor cells (MPNST) and induced cell death at a 10-fold lower concentration than 2-ME. Furthermore, STX 3451 treatment not only caused microtubule disruption but also affected the actin-based cytoskeleton through disruption of the long microfilaments and reorganization of actin molecules through depolymerization.…”
Section: Discussionmentioning
confidence: 99%
“…STX 3451 exposure increased the activation of caspase-3 in ST88 cells which indicated the induction of the apoptotic cell death pathway. 21 In addition, STX 3451 affected the phosphorylation of PI3K and mTOR pathways through inhibiting Akt phosphorylation, a pathway implicated in the induction of apoptosis as well as in the regulation of autophagy. 21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations